PENERAPAN SISTEM AKUNTANSI PERTANGGUNGJAWABAN TERHADAP PENGENDALIAN BIAYA PADA PT. PUPUK SRIWIJAYA PALEMBANG - RENDRA BAKTI; NINA SABRINA (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2021)
This study aims to determine the effect of the application of a responsibility accounting system on the cost control of PT Pupuk Sriwidjaya Palembang. This research includes causality research. There is one independent variable, namely the responsibility accounting system, and one dependent variable, namely cost control. The sample in this study was the employees of the Accounting Department and the Budget Department of PT Pusri Sriwidjaya Palembang in 2020, amounting to 43 people. The data used in this study are primary data. The data analysis technique used descriptive simple linear regression. The results of the study concluded that there was an effect of the application of a responsible accounting system on cost control at PT Pupuk Sriwidjaya Palembang, with the percentage of influence being 90.40%, and 9.60% influenced by other factors